2016
DOI: 10.1111/jfpp.12737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Treatment on Changes of Respiration Rate and Enzyme Activity of Ivory Mangoes During Storage

Abstract: Mango is produced in tropical zone and consumed around the world. However, mango fruit has a short postharvest life resulting in severe loss during storage. In this study, the effects of heat treatment applied to ivory mangoes on physical, physiological and biochemical quality was studied. The results showed that mangoes subjected to all hot water treatment at 50C -10 min, 60C -1 min, 70C -5 s could improve the quality, while the 60C -1 min treatment was the optimal method. We found that 60C -1 min treatment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
(24 reference statements)
0
10
1
Order By: Relevance
“…Enzymes such as PG, βgalactosidase, α-mannosidase, and β-hexosaminidase are involved in cell wall modification and softening in mango fruit (Abu-Sarra and Abu-Goukhi, 1992;Hossain et al, 2014). HWT (60°C for 1 minute) inhibits the cell wall degrading enzyme PG after ten days of storage at 25°C (Wang et al, 2016). Previous studies by Ketsa et al (1998) revealed that HWT at 33°C for three days increased the activity of β-galactosidase caused in 'Nam Dokmai' mango after eight days of storage at 25°C.…”
Section: Hot Water Treatmentmentioning
confidence: 96%
See 2 more Smart Citations
“…Enzymes such as PG, βgalactosidase, α-mannosidase, and β-hexosaminidase are involved in cell wall modification and softening in mango fruit (Abu-Sarra and Abu-Goukhi, 1992;Hossain et al, 2014). HWT (60°C for 1 minute) inhibits the cell wall degrading enzyme PG after ten days of storage at 25°C (Wang et al, 2016). Previous studies by Ketsa et al (1998) revealed that HWT at 33°C for three days increased the activity of β-galactosidase caused in 'Nam Dokmai' mango after eight days of storage at 25°C.…”
Section: Hot Water Treatmentmentioning
confidence: 96%
“…For instance, HWT at 55°C for ten-minutes suppressed respiration in 'Tainong' mango fruit during storage at 20°C for six days (Zhang et al, 2012). Similarly, studies on 'Ivory' mango revealed that hot water treatment at 60°C for one-minute inhibited ethylene production and respiration rate (Wang et al, 2016). The efficacy of HWT is strongly linked to its potential to regulate key enzymatic activities affecting quality attributes of fresh horticultural produce.…”
Section: Hot Water Treatmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Increase in phenolic content might be due to change in cellular structure, improved enzymatic activity due to higher temperature (Lorinda et al, 1987). Earlier finding by Wang et al (2017) described that higher TPC was observed in Ivory mango when heated at 60°C for 1 min. Likewise, mango fruits treated with hot water treatments showed higher TPC as compared to control fruits (Hasan et al, 2020).…”
Section: Discussionmentioning
confidence: 81%
“…However, the rising trend of relative electrical conductivity was most significantly suppressed in response to the combined treatment in Fig. (B), and this result was similar to the historical record reported by Hui Wang . One explanation was that HT and HT + AT regulated the metabolism of ROS to maintain low oxidative toxicity, which had a positive relation to the high production of MDA and relative electrical conductivity.…”
Section: Discussionmentioning
confidence: 99%